Prevalence and correlates of common mental disorders in people living with HIV in primary health care facilities in Ekurhuleni district - Aniekan Edet; Samuel Agbo; Afolake A. Amodu; Nwabisa N. Edet (AOSIS, 2024)
Background: There is paucity of data regarding the prevalence of common mental disorders (CMDs) in people living with HIV (PLHIV) in Ekurhuleni Health District (EHD), South Africa. Also, there is an association between CMDs and poor HIV treatment outcomes. Guidelines therefore recommend that healthcare practitioners screen for CMDs in PLHIV. Aim: To determine the prevalence and correlates of CMDs in PLHIV in primary health care facilities in Ekurhuleni district. Setting: Seven primary health facilities in Ekurhuleni district. Methods: A cross-sectional study was conducted in which data were collected from 403 randomly selected participants, using a questionnaire that incorporated the scores of the Patient Health Questionnaire (PHQ)-9, generalised anxiety disorder (GAD)-7 and substance use disorder (SUD) criteria of Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM 5). The proportion screening positive for CMDs was calculated. 'R' statistical software was used for univariate and multivariate analysis, with a confidence interval (CI) of 95%. Results: Most participants (63%) were female and the mean age was 43 ± 11 years. Forty per cent of participants screened positive for CMDs, 16.6%, 15.1% and 24.1% screened positive for depression, GAD and SUD, respectively. Common mental disorders were associated with poor adherence and HIV non-suppression, while increasing age and being female were associated with reduced risk of CMDs. The risk of severe SUDs in males was 11 times compared to females. During assessment, clinicians screened only 16%, 14% and 40% of the cohort for depression, GAD and SUDs, respectively. Conclusion: The prevalence of CMDs remains high. Adherence to recommendations to screen for CMDs in PLHIV is low. Contribution: This study reveals a low CMD screening rate, estimates the prevalence of CMDs in PLHIV in Ekurhuleni district, and its impact.